(untitled) (Global Journal of Human-Social Science, 2018)
Bangladesh is the fastest developing country in the world today Among various sectors responsible for this contribution the highest important is garments or RMG The generation of foreign currency employment opportunity are the basics done by RMG at present Most of this employment is poor women workforce at a very little cost While the garments sector is dependent on this labor force the employers are not providing them the facilities according to labor law Women s social occupational rights are at risk today This study has gone through the observation of women workers social safety security conditions with the solution of the problems prevailing in RMG sector